Pediatric underdosing of efavirenz: a pharmacokinetic study in Uganda. - Fillekes, Q; Natukunda, E; Balungi, J; Kendall, L; Bwakura-Dangarembizi, M; Keishanyu, R; Ferrier, A; Lutakome, J; Gibb, D; Burger, D; Walker, A (2011)
OBJECTIVES: To evaluate international pediatric efavirenz dosing recommendations using full pharmacokinetic (PK) information. DESIGN: Open-label, multicenter, PK study. METHODS: Forty-one HIV-infected Ugandan children (3-12 years) on efavirenz + lamivudine + abacavir were enrolled in a study of twice-daily to once-daily lamivudine + abacavir 36 weeks after antiretroviral therapy initiation in the ARROW trial. Once-daily efavirenz doses were 200, 250, 300, 350 mg for children weighing 10 to <15, 15 to <20, 20 to <25, 25 to <30 kg, respectively, using 200/50 mg capsules or halved 600 mg tablets in case of 300 and 350 mg doses. Intensive plasma PK sampling (t = 0, 1, 2, 4, 6, 8, 12 hours postobserved ingestion) was performed at steady state (PK1) and repeated 4 weeks later (PK2, including a further 24-hour sample). RESULTS: Forty-one and 39 children had evaluable efavirenz profiles at PK1 and PK2, respectively. Seventeen (41%) were boys. Five, 16, 17, 3 were in the 10 to <15, 15 to <20, 20 to <25, 25 to <30 kg weight bands. The geometric mean (%CV) the area under the concentration-time curve 0-24 hours postdose was 50.8 (90.8%) and 55.5 (82.7%) h·mg·L(-1) at PK1 and PK2, respectively. Six children at PK1 and 7 at PK2 had subtherapeutic C(8h) and/or C(12h) (<1.0 mg/L), 7 of 41 (17%) at either visit. At PK2, 15 of 39 (38%) children had C(24h) <1.0 mg/L (median (interquartile range) [range] 1.1 (0.7-2.9) [0.3-18.4]). Ten children at PK1 and 11 at PK2 had C(8h) and/or C(12h) >4.0 mg/L; 12 of 41 (29%) at either visit. CONCLUSIONS: African children aged 3-12 years, on efavirenz dosed according to 2006 WHO/manufacturer's recommendations, had lower and highly variable efavirenz PK parameters compared with adult data from manufacturer's leaflet. There were no differences across weight bands, suggesting no major effect of using half tablets. Higher pediatric efavirenz doses, as per WHO 2010 recommendations, should be used and investigated further but may risk increasing the proportion of children with potentially toxic levels.